What Do Family Caregivers of Alzheimer’s Disease Patients Desire in Smart Home Technologies? - Rialle, V.; Ollivet, C.; Guigui, C.; Hervé, C. (Methods of Information in Medicine, 2008)
Objectives: The authors’ aim was to investigate the representations, wishes, and fears of family caregivers (FCs) regarding 14 innovative technologies (IT) for care aiding and burden alleviation, given the severe physical and psychological stress induced by dementia care, and the very slow uptake of these technologies in our society.Methods:A cluster sample survey based on a selfadministered questionnaire was carried out on data collected from 270 families of patients with Alzheimer’s disease or related disorders, located in the greater Paris area. Multiple Correspondence Analysis was used in addition to usual statistical tests to identify homogenous FCs clusters concerning the appreciation or rejection of the considered technologies.Results: Two opposite clusters were clearly defined: FCs in favor of a substantial use of technology, and those rather or totally hostile. Furthermore the distributions of almost all the answers of appreciations were U-shaped. Significant relations were demonstrated between IT appreciation and FC‘s family or gender statuses (e.g., female FCs appreciated a tracking device for quick recovering of wandering patients more than male FCs: p = 0.0025, N = 195).Conclusions: The study provides further evidence of the contrasted perception of technology in dementia care at home, and suggests the development of public debates based on rigorous assessment of practices and a strict ethical aim to protect against misuse.
Keywords: Smart homes; dementia care; Alzheimer’s disease; family caregivers; acceptability